The Mystery of Capital or the Mystification of Capital? - Obeng-Odoom, Franklin (Review of Social Economy, 2013)
In contemporary political economic analyses of development processes, Hernando De Soto'sThe Mystery of Capital, has been one of the most discussed, albeit controversial, books. Although well received by global development agencies such as the World Bank, a key exponent of De Soto's work, positing that the creation and institutionalisation of individual property in housing and land revives “dead capital” and creates the conditions that will enable the poor to emerge from abject poverty, has been widely criticised. These criticisms show that (1) the thesis is flawed, (2) the flaw is due to implementational problems and (3) the practical implications arising from the thesis are largely neutral and will neither improve nor worsen poverty. Although agreeing with the first criticism, this paper argues that the second critique must be nuanced, and the third is entirely mistaken. Utilising insights from Joseph Schumpeter, Karl Polanyi and Henry George, it makes the case that applying De Soto's ideas through policy would be ineffective in curbing urban poverty, and actually serve to simultaneously entrench and augment it. Moreover, while finding that De Soto's assumption that the poor possess some economic agency is sound and may, indeed, secure socially beneficial outcomes through pursuing innovative and entrepreneurial endeavours, De Soto's conception of such processes remains largely emasculated from broader political economic considerations.
Keywords: dead capital; economic research; fictitious commodities; fictitious commodity; political economic analysis; poverty; progress amid poverty; property; social innovation

Promoting Freedom of Association in China? Putting Transnational Corporate Social Responsibility into a National Context - Chan, Chris King-Chi (Journal of Comparative Asian Development, 2013)
Using the findings of an intensive case study of a corporate social responsibility (CSR) project in China, this paper argues against the view that CSR and the state's regulations are mutually exclusive. It contests that the theorization of the transnational social movement (TSM) should not ignore the development of the state regime, which in turn is shaped by the power relations in the workplace and the community, and is embedded in the national political history. The findings of this research support the Polanyi-inspired approach which sees CSR as being embedded in the changing patterns of business–government–society relations. This approach highlights that the behaviour of the state and the engagement of civil society have actively shaped the scope and the implementation of CSR. Following this line of argument, this paper provides evidence of the dynamics and paradox of workers' and grassroots NGOs' engagement in CSR in China. The specificity of China stems from the state, on the road of China's transition from a state socialist country to being a part of global capitalism. Workers' and NGOs' frustration at the denial of freedom of association (FOA) under the CSR projects at this stage reflects well the legacy of Chinese state socialism, in particular the nature of the official trade unions and the suppressive function of the local state–global capital nexus. Therefore, the state is by no means being excluded from either business or civil society, as the orthodox view of CSR presumes.
Keywords: CSR; China; NGOs; corporate social responsibility; delegated legislation; freedom of association; labor unions; labour unions; migrant labor; migrant labour; migrant workers; nongovernmental organizations; social responsibility of business; workers’ committee

Socioéconomie et démocratie, l'actualité de Karl Polanyi - Hillenkamp, Isabelle; Laville, Jean-Louis (Toulouse : Érès éd, 2013)
La crise actuelle révèle des tensions fondamentales entre capitalisme et démocratie. L'orthodoxie occidentale, centrée sur les programmes d'ajustement, s'avère incapable d'affronter ce défi à la frontière de l'économie, du social et du politique. Il est temps de se tourner vers d'autres approches. S'appuyant sur l'oeuvre singulière de Karl Polanyi (1886- 1964) qui a décelé la dérive totalitaire de la société de marché, cet ouvrage soumet de nouvelles clés pour penser certains des problèmes les plus ardus de notre temps. Les auteurs, internationalement reconnus, venant d'Amérique et d'Europe, du Sud et du Nord, sont publiés pour la première fois ensemble en langue française. Ils proposent une vision croisée des rapports entre démocratie et économie, à partir de différentes disciplines et de divers terrains d'étude. Cette réflexion collective débouche sur la construction d'un cadre théorique permettant de comprendre la teneur des mutations économiques et politiques contemporaines. Mais elle ne s'arrête pas aux constats critiques. Face à la menace d'une régression autoritaire, elle s'intéresse aux pratiques qui concrétisent des issues solidaires et démocratiques à la crise. ENG: The aim of this book is to mobilize the contribution of Polanyi to think the socio-economy in a perspective of deepening democracy. The book updates the critical analysis of the new globalized capitalism but also identifies socio-economic experiences that can contribute to building more democratic societies in the 21st century.
Keywords: démocratie; développement économique - aspect social; economics - sociological aspects; triple movement; économie de marché; économie politique - aspect sociologique; économie sociale; économie sociale et solidaire